ANALISIS KELAYAKAN INVESTASI PERLUASAN USAHA PADA D’ MARKAZ COFFEE - Nahdah, Na'ilah; Rustam, Andi; Adiningrat, Andi Arifwangsa (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to determine the investment feasibility analysis method can determine whether or not business expansion at D’Markaz Coffee is feasible. The sample in the study was taken from the financial statements for the period 2023-2024. In this study, the data sources used include primary data. The method used is a quantitative descriptive approach using the investment feasibility analysis method, namely Net Present Value, Internal Rate Of Return, Average Rate of Return and Payback Period. The results of the study showed that D’Markaz Coffee is feasible, because it produces a positive NPV value of IDR 5,199,879, IRR 11.73% which is higher than the discount rate of 10%, ARR of 44.21% exceeds the expected profit level and a short Payback Period of 1 year 9 months. Thus, business expansion at D’Markaz Coffee is feasible to be done. Keywords: Investment Feasibility, Business Expansion, D’Markaz Coffee